Perspektif Etos Kerja Islami dalam Menunjang Kinerja Karyawan Perguruan Tinggi Islam Kota Malang - Basalamah, Muhammad Ridwan; Solehuddin, Sulton (Universitas Islam Malang, 2017)
Man is commanded to behave in accordance with the moral ethics, (guidance) contained in the Quran. Included in the work should also pay attention to ethics in accordance with Islamic Sharia. Ethics is a set of values about good, right, bad, and wrong based on the principles of morality, especially in behavior and action. So that ethics is one important factor for the creation of a better human living conditions. This study aims to provide empirical evidence about the perspective of Islamic work ethic in supporting employee performance in Islamic universities Malang city. Population in this research is permanent employee at Islamic university in Malang city consisting of Unisma, UIN, UMM has been working for a year. The analysis tool used in this research is SPSS 23.0 (statistical Product and Service Solutions). The results showed that the variables of Islamic work ethic simultaneously have a positive and significant effect on employee performance. The most influential indicator is Al-Muhajadah or hard work of 48.2%. This is because every employee must be able to work hard in completing the task well